Pengaruh Disregulasi Emosi Terhadap Kecenderungan Perilaku Nonsuicidal Self-Injury Pada Mahasiswa Di Kota Makassar - Qurrata Ayuni Safruddin; Widyastuti Widyastuti (CV. ULIL ALBAB CORP, 2025)
The phenomenon of a tendency towards non-suicidal self-injury behavior which often occurs recently among students. This phenomenon is caused by emotional dysregulation experienced by students which is caused by several psychological pressures that students feel. The purpose of this research is to see whether there is an influence of emotional dysregulation on the tendency to engage in NSSI behavior among students in the city of Makassar. This research uses ordinal regression analysis techniques. Participants in this research were 164 students who were obtained using the accidental sampling technique. The results of the analysis show a Nagelkerke score of 0.320, which means that emotional dysregulation contributes 32% of the variation. The significance value obtained was 0.001 (p<0.05), which means that emotional dysregulation can be a significant predictor of NSSI behavioral tendencies. The results of additional analyzes conducted showed that there were significant differences between NSSI behavior tendencies based on gender. However, based on age, there was no significant difference between NSSI behavior. And the results of additional tests on emotional dysregulation show that there are no significant differences based on gender or age group. The implications of this research are expected to be able to increase insight and knowledge regarding emotional dysregulation which should not occur in subjects and subjects are able to regulate their emotions well without carrying out maladaptive coping actions such as NSSI.